Yanomami : the fierce controversy and what we might learn from it - Borofsky, Robert, 1944- (California series in public anthropology, 2005)
Yanomami raises questions central to the field of anthropology - questions concerning the practice of fieldwork, the production of knowledge, and anthropology's intellectual and ethical vision of itself. Using the Yanomami controversy - one of anthropology's most famous and explosive imbroglios - as its starting point, this books considers how fieldwork is done, how professional credibility and integrity are maintained, and how the discipline might change to address central theoretical and methodological problems. Both the most up-to-date and thorough public discussion of the Yanomami controve.